Strategies to Improve Purchasing Decisions through Understanding Price Perceptions in Society - Dewi Lestari; Ulfi Yanti Harahap; Azhari Akmal Tarigan; Nuri Aslami (Proceeding International Conference on Islamic Economics Community Services (ICIECS), 2023)
This study explores how consumer trust affects purchasing decisions on Indonesia's Shopee e-commerce platform. With the rise of online shopping, trust has become crucial in consumer behavior. The research addresses the gap in understanding trust's influence in online marketplaces by evaluating the perspectives of 150 active Shopee users and 50 sellers through a mixed-method approach. The findings reveal that trust is a key factor in purchasing decisions, driving sales and customer loyalty. Educational efforts on transparency, product authenticity, and responsive customer service, along with government collaboration for education and security, effectively build trust. The study concludes that maintaining consumer trust, supported by government partnerships, is vital for Shopee's market competitiveness. The implications suggest that emphasizing trust not only enhances customer retention but also supports long-term business growth